“How to tell them that I no longer inhabit this body?” An anthropological analysis on corporal dimension in concentrationary experiences - Tello Weiss, Mariana (Revista de Antropología Social, 2022)
Adopting an anthropological perspective, this article analyses the role corporality plays in the memories of survivors of the clandestine detention centre known as “La Perla” (Córdoba, Argentina). It engages with the role of bodies in narrating extreme situations and with the corporal dimension of memory itself. It asks how bodies make and transmit memory in these accounts. Based on testimonies and fieldwork’s notes, the article scrutinises the policy of “disappearing” the bodies and “disciplining” them through torture. Finally, it investigates how this past treatment of the body bleeds into the present – in how these memories are (d)enounced, and in the everyday lives of the survivors.
Keywords: Bodies; violences; memories; Clandestine Detention Centres